Illocutionary Acts in the Hashtag #KaburAjaDulu: A Cyber Activism Discourse Study on Social Media X - Eureka Jovita Br Panjaitan; Friska Br Tambunan; Murni Nur Fitriyani; Kerwin; Rahmadsyah Rangkuti (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2025)
Emerging as a digital reaction to economic hardship, and later as a form of political critique, this hashtag represents the dynamic nature of public discourse in Indonesia. This study analyzes how language functions as a performative instrument in online activism through the hashtag #KaburAjaDulu on the social media platform X (formerly Twitter). This study uses a mixed-methods approach that combining qualitative and quantitative analyses based on Searle's Speech Act Theory. Data were collected from influencer accounts verified with a blue checkmark or having more than 2,000 followers on their personal accounts on X during two viral periods in 2025 (February and September) to identify and classify the illocutionary acts used by social media users. These findings reveal variations in how illocutionary acts construct collective meaning and reflect public sentiment across various ongoing sociopolitical contexts. This study found that assertive illocutionary acts were the most dominant, followed by Directive, Expressive, and Commissive illocutionary acts. Rather than being a mere linguistic phenomenon, the hashtag functions as a space in which individual emotions, social critique, the expression of aspirations, and political awareness converge. This study highlights the evolving relationship between language, digital communication, and social psychology, providing new insights into how online expressions can mobilize discourse and shape collective attitudes in a digital society.